2005
DOI: 10.1007/s00384-005-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the expression of Wnt-1, WISP-1, survivin and cyclin-D1 in colorectal carcinoma

Abstract: Overexpression and interplay between Wnt-1, WISP-1, survivin and cyclin-D1 may play a role in tumorigenesis, possibly by promoting cell cycle checkpoint progression, accelerating cell growth and inhibiting apoptosis. Our data may provide useful information towards the search for potent therapeutic targets towards the development of novel treatment strategies for CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 27 publications
3
37
1
Order By: Relevance
“…This observation suggests that restriction of cyclin D1 to the cytoplasm may allow suppression of cellular proliferation but requires a more rigorous investigation. Interestingly, a number of colorectal cancer studies have observed cytoplasmic cyclin D1 in tumour specimens (Palmqvist et al, 1998;Handa et al, 1999;McKay et al, 2000;Holland et al, 2001;Khor et al, 2006;Kuramochi et al, 2006) and at least one of these studies has reported that increased cytoplasmic cyclin D1 correlated with low proliferation (Palmqvist et al, 1998). This result is similar to our analyses ( Figure 4C), wherein tumours with predominately cytoplasmic cyclin D1 showed a significantly lower proliferative index.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation suggests that restriction of cyclin D1 to the cytoplasm may allow suppression of cellular proliferation but requires a more rigorous investigation. Interestingly, a number of colorectal cancer studies have observed cytoplasmic cyclin D1 in tumour specimens (Palmqvist et al, 1998;Handa et al, 1999;McKay et al, 2000;Holland et al, 2001;Khor et al, 2006;Kuramochi et al, 2006) and at least one of these studies has reported that increased cytoplasmic cyclin D1 correlated with low proliferation (Palmqvist et al, 1998). This result is similar to our analyses ( Figure 4C), wherein tumours with predominately cytoplasmic cyclin D1 showed a significantly lower proliferative index.…”
Section: Discussionsupporting
confidence: 90%
“…The present finding that prostate cancer cells frequently exhibit cytoplasmic cyclin D1 is novel, but not without precedent. For example, elevated cyclin D1 with cytoplasmic cyclin D1 staining has been reported in many different tumour types, such as colorectal (Handa et al, 1999;Khor et al, 2006), pancreatic (Culhaci et al, 2005), lung (Dworakowska et al, 2005), thyroid (Temmim et al, 2006), and bladder (Sudo et al, 2003). Despite these observations only a handful of studies have addressed the functional consequence of cytoplasmic cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a strong Wnt-1 staining in the normal colonic epithelium, while in the majority of primary tumors the expression was decreased. By contrast, Khor et al (16) revealed in 47 colorectal tissue samples that intratumoral protein expression of Wnt-1 was significantly increased in the primary tumor compared with the normal epithelium. Finally, Holcombe et al (17) revealed in CRC that Wnt-1 is expressed equally and strongly in normal and malignant colon tissues.…”
Section: Discussionmentioning
confidence: 86%
“…Posterior studies using RT-PCR and immunohistochemistry involving newer antibodies and reagents have revealed the presence of survivin in non-tumorous tissues, especially in colon mucosa adjacent to carcinomas (21,22,52). One of these experiments involved the same reagent used in the present study (52).…”
Section: Discussionmentioning
confidence: 91%